2010
DOI: 10.1111/j.1538-7836.2010.03972.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double‐blind comparison of effects of abiciximab bolus only vs. on‐label regimen on ex vivo inhibition of platelet aggregation in responders to clopidogrel undergoing coronary stenting

Abstract: Summary. Background: On top of aspirin, an abciximab bolusonly regimen results in a 30% drop in platelet inhibition at 6 h as compared with the on-label regimen. The concomitant administration of high loading dose clopidogrel, by bridging with abciximab bolus, may sustain suppression of platelet activity over time. Objectives: To investigate the non-inferiority of abciximab bolus-only and concomitant high loading dose clopidogrel vs. abciximab bolus + infusion with respect to the inhibition of platelet aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…There is recent evidence that administration of eptifibatide in this setting results in profound platelet inhibition for at least 22 h 81. Similarly, it has been demonstrated in patients with STEMI and no cardiac arrest that a bolus of abciximab without additional infusion might be sufficient 82. Cangrelor, a novel intravenous P2Y12 inhibitor, is a promising agent in this setting due to its rapid onset (and offset) of action and its effectiveness in platelet inhibition,83 but data are lacking.…”
Section: Is Immediate Cag Recommended For All Oohca Survivors?mentioning
confidence: 99%
“…There is recent evidence that administration of eptifibatide in this setting results in profound platelet inhibition for at least 22 h 81. Similarly, it has been demonstrated in patients with STEMI and no cardiac arrest that a bolus of abciximab without additional infusion might be sufficient 82. Cangrelor, a novel intravenous P2Y12 inhibitor, is a promising agent in this setting due to its rapid onset (and offset) of action and its effectiveness in platelet inhibition,83 but data are lacking.…”
Section: Is Immediate Cag Recommended For All Oohca Survivors?mentioning
confidence: 99%
“…However, a recent study showed that withholding abciximab maintenance infusion does not impair platelet inhibition in patients receiving a 600 mg loading dose of clopidogrel 38. Similarly, Christ et al have shown that intracoronary abciximab bolus-only administration with oral P2Y 12 inhibitor (600 mg of clopidogrel or 60 mg of prasugrel) initiation effectively inhibited overall platelet reactivity for at least 48 hours, which brings the value of continuous abciximab infusion into question 39.…”
Section: Other Abciximab Administration Strategiesmentioning
confidence: 99%
“…In EPILOG, the successor to EPIC, heparin doses were reduced to the currently recommended bolus dose of 70 IU/kg (2). A recent study even showed that withholding abciximab maintenance infusion does not impair platelet inhibition in patients receiving a high loading dose of clopidogrel (21). Abciximab is eliminated through the reticuloendothelial system, including the spleen, and does not require dose adjustment in the setting of renal insufficiency (ǠTable 1) (22).…”
Section: Dosing and Administrationmentioning
confidence: 99%